Simultaneous Single-Pulse Observations of Radio Pulsars: V. On the Broadband Nature of The Pulse Nulling Phenomenon in PSR B1133+16 - Bhat, N; Gupta, Y; Kramer, M; Karastergiou, A; Lyne, A; Johnston, S (2006)
We revisit the phenomenon of pulse nulling using high-quality single-pulse data of PSR B1133+16 from simultaneous multifrequency observations. Observations were made at 325, 610, 1400 and 4850 MHz as part of a joint program between the European Pulsar Network and the Giant Metrewave Radio Telescope. The pulse energy time series are analysed to derive improved statistics of nulling pulses as well as to investigate the frequency dependence of the phenomenon. The pulsar is observed to be in null state for approximately 15% of the time; however, we find that nulling does not always occur simultaneously at all four frequencies of observation. We characterise this "selective nulling'' as a function of frequency, separation in frequency, and combination of frequencies. The most remarkable case is a significantly large number of nulls ($≈$6%) at lower frequencies, that are marked by the presence of a fairly narrow emission feature at the highest frequency of 4850 MHz. We refer to these as "low frequency (LF) nulls." Our analysis shows that this high frequency emission tends to occur preferentially over a narrow range in longitude and with pulse widths typically of the order of a few milliseconds. We discuss the implications of our results for the pulsar emission mechanism in general and for the broadbandness of nulling phenomenon in particular. Our results signify the presence of an additional process of emission which does not turn off when the pulsar nulls at low frequencies, and becomes more prominent at higher frequencies. Our analysis also hints at a possible outer gap origin for this new population of pulses, and thus a likely connection to some high-energy emission processes that occur in the outer parts of the pulsar magnetosphere.